Between information literacy and the digital divide: Exploring a reconceptualization of the digital exclusion phenomenon - Zapata, Cristian Berrío [UNESP] (My University, 2012)
This article analyzes the evolution of the concepts I-literacy, E-literacy, informational alphabetization (ALFIN as in Spanish) and Digital Divide, to find a common ground to complement conceptually the measuring of the divide. The convergence process between I-Literacy and E-Literacy has been retrieved, reaching the final concept of informational alphabetization (ALFIN as acronym of the Spanish expression ALFabetización INformacional). To propose its differentiation into three levels: the basic level of verbal-technological codification, second level for meta-analysis, and upper level for ethical-critical action. This proposal aims to rethink the digital divide, raising questions about the meaning of measurement, and the necessary precautions to avoid confusing measurement with assimilation. We state that the concept of information literacy (ALFIN - informational alphabetization) should feed the study of the Digital Divide, and describe how this could affect the pyramid model of ICT appropriation developed by the author. In further research about digital exclusion The Pandora's box quality of the Web is emphasized. It can reinforce exclusion, threatens democracy and freedom in the absence of a literate digital citizen, if further simplification is carried under the access-to-infrastructure model, if the citizens' formation in capabilities that exceed the instrumental. We conclude that measuring these meta-analysis and ethical-critical action skills is the advisable way to build a metric for the digital divide. We warn about the possibility of finding a second-order divide much larger and complex than the access divide.
Entre la alfabetización informacional y la brecha digital: Reflexiones para una reconceptualización de los fenómenos de exclusión digital
Keywords: ALFIN; Digital divide; E-literacy; I-Literacy; Information literacy